Systemic Comorbidities in Patients with Primary Fascial Space Infections of Odontogenic Orogin: Experience of a Tertiary Care Center - Annum Zamir; Sara Ali; Saima Khan; Yasir Rehman Khattak; Sheema; Anum Wajid; Jawad Ullah Khattak (Gandhara University, 2023)
OBJECTIVES To assess systemic immune-compromised comorbidities in patients presenting with odontogenic infections that extend to fascial spaces. This study was designed to investigate the incidence of immune-compromising systemic comorbidities among patient presenting with odontogenic infections. METHODOLOGY This cross-sectional study was performed at the Department of Maxillofacial Surgery, Hayatabad Medical Complex (HMC) Peshawar from October 2018 through April 2019. However, patients older than 10 years of age, presenting with fascial space infections other than odontogenic cause, secondary fascial space infections and patients with multiple organ failure were excluded. The odontogenic infections were categorized according to their anatomical location. The prevalence of comorbidities was also assessed. RESULTS A total of 145 patients were included, where the male to female ratio was 3.8:1, mean age ~ 56 ± 14.74 years (range: 12-80 years) and mean duration of the odontogenic infections was 5± 1.2 days. The submandibular space was the most frequent site involved in odontogenic infections with a frequency of 60 (41.4%), followed by buccal space with 44 (30.3%) patients &    canine space with 31 (21.4%) patients. Of the 79 patients with comorbidities out of total 145 patients, diabetes mellitus was recorded in 60 patients. Other comorbidities included hypertension, renal and hepatic impairment. CONCLUSION Diabetes mellitus was the most common immune compromising comorbidity presented in patients with odontogenic infections extending in fascial spaces. Assessment of diabetes in routine dental practice is emphasized to avoid exacerbation of the odontogenic infections.